KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU - Bejo Bejo (Manajer Pendididikan, 2015)
The objective of this study to describe the leadership in increasing teachers’ discipline at senior high school 1 Lubuklinggau city. The subject of research are principal, teachers and student. This research used descriptive qualitative method and two techniques in collecting data: interview and documentation.The technique for analyzing the data is using reductive data, display data, conclusion, and verification data. The conclusion is that the principal leadership in increasing teachers’ discipline has been done professionally based on the role and function, so that theteachers’ discipline has been done well and the vision and mission can be achieved.Key words: leadership, principal, discipline, teacher